Some factors affecting transformation of Aspergillus nidulans - Problems and progress. - S. G. Shawcross; P. Hooley; P. Strike (Fungal Genetics Reports, 1987)
Some factors affecting transformation of Aspergillus nidulans - Problems and progress.